Pluralité des parcours des étudiants ouest-africains en Chine - Sylvie Bredeloup (Les éditions de la Maison des sciences de l'Homme, 2014)
China is becoming a new centre of attraction of the African student mobility, attributing an increasing number of scholarships within the framework of its new Sino-African policy of cooperation. This paper questions the evolution of the careers of the nationals of sub-Saharan Africa trained in China, in connection with the economic opening of the Asian giant but also with the generalized hardening of the migratory policies. The first generations welcomed in the name of "communist internationalism" usually returned to their home country to put advantage their skills soon after the completion of their post-graduate qualifications. The following generations take advantage of their multiple skills to introduce new South-South commercial partnerships. The mobilities for studying obey not only institutional logics; they can also depend on individual strategies, themselves widely influenced by the new globalized models of consumption and success.